A humán erőforrás mendzsment funkciók fejlődése 1. rész: A "társadalmi reformerek” szakaszának és a "szociálpolitikai koncepció” szakaszának jellemzői = Development of function of human resource management - Gulyás, László; Turcsányi, Enikő (Közép-Európai Közlemények, 2017)
According to Torrington-Hall, the HR-functions developed six phases, from the industrial revolution to present day. In our paper we analyze the development of functions of humán resource management. Our essay consists of three parts. In the first part of this essay we survey the features of first phase - this is called social reformers - in England. In the second part of this essay we survey the features of second phase - this called “welfare personnel” - in England. In the third part of this essay we present features of the first and the second phase in dualist Hungary (1867-1918).